A Pleomorphic Puzzle: Heterogeneous Pulmonary Vascular Occlusions in Patients with COVID-19 - Singh, Jeeshan; Herrmann, Irmgard; Mahajan, Aparna; Schauer, Christine; Shan, Xiaomei; Hartmann, Arndt; Rieker, Ralf; Evert, Katja; Falkeis, Christina; Naschberger, Elisabeth; von Stillfried, Saskia; Boor, Peter; et al. (International Journal of Molecular Sciences, 2022)
Vascular occlusions in patients with coronavirus diseases 2019 (COVID-19) have been frequently reported in severe outcomes mainly due to a dysregulation of neutrophils mediating neutrophil extracellular trap (NET) formation. Lung specimens from patients with COVID-19 have previously shown a dynamic morphology, categorized into three types of pleomorphic occurrence based on histological findings in this study. These vascular occlusions in lung specimens were also detected using native endogenous fluorescence or NEF in a label-free method. The three types of vascular occlusions exhibit morphology of DNA rich neutrophil elastase (NE) poor (type I), NE rich DNA poor (type II), and DNA and NE rich (type III) cohort of eleven patients with six males and five females. Age and gender have been presented in this study as influencing variables linking the occurrence of several occlusions with pleomorphic contents within a patient specimen and amongst them. This study reports the categorization of pleomorphic occlusions in patients with COVID-19 and the detection of these occlusions in a label-free method utilizing NEF.
CRIS-Team Scopus Importer:2022-12-23
Keywords: age; COVID-19; gender; immunothrombosis; native endogenous fluorescence; occlusions; pleomorphism; SARS-CoV-2